2022
DOI: 10.1371/journal.pcbi.1010326
|View full text |Cite
|
Sign up to set email alerts
|

The computational relationship between reinforcement learning, social inference, and paranoia

Abstract: Theoretical accounts suggest heightened uncertainty about the state of the world underpin aberrant belief updates, which in turn increase the risk of developing a persecutory delusion. However, this raises the question as to how an agent’s uncertainty may relate to the precise phenomenology of paranoia, as opposed to other qualitatively different forms of belief. We tested whether the same population (n = 693) responded similarly to non-social and social contingency changes in a probabilistic reversal learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 63 publications
(115 reference statements)
2
40
0
Order By: Relevance
“…We note that previous work showed a Bayesian instantiation of this attributional model outperformed associative model variants [31]. Model 1 allowed separate uncertainties and likelihood weights for each attribution, identical to our prior work [31]; this model demonstrated that trait paranoia increased belief rigidity and self-other inconsistency, and by extension, may serve as a useful assay to test the mechanisms of haloperidol which is theorised to reduced paranoia. In line with general theories of belief updating [37], Model 2 hypothesised that beliefs would be updating with the same likelihood weight.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…We note that previous work showed a Bayesian instantiation of this attributional model outperformed associative model variants [31]. Model 1 allowed separate uncertainties and likelihood weights for each attribution, identical to our prior work [31]; this model demonstrated that trait paranoia increased belief rigidity and self-other inconsistency, and by extension, may serve as a useful assay to test the mechanisms of haloperidol which is theorised to reduced paranoia. In line with general theories of belief updating [37], Model 2 hypothesised that beliefs would be updating with the same likelihood weight.…”
Section: Discussionsupporting
confidence: 55%
“…Current models include mechanistic explanations for perceived changes in the harmful intent and self-interest that might motivate the actions of another. Prior work suggests high trait paranoia is associated with rigid priors about the harmful intent of partners, and a belief that a partner’s actions are not consistent with their true intentions (Barnby et al, 2020b; 2022a). Several predictions can be made concerning the influence of dopamine D2/D3 antagonism on paranoia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this mechanism may not be specifically tied to social contexts, but instead may be related to a more general deficit in learning under uncertainty (Reed et al, 2020; Suthaharan et al, 2021). However, we do note that the social control task employed by Suthaharan et al (2021) was not as ecologically valid as other tasks that were used to study paranoia such as the dictator game (Raihani and Bell, 2017; Barnby et al, 2020, 2022) or our task which was adapted from empirically-observed human-human interactions in a previous study using videos of human advisers intending to either help or deceive players (Diaconescu et al, 2014). Finally, it is also possible that there are both domain-general and domain-specific changes, but that these can only be studied at the neuronal level and converge on the same behavioural model parameters.…”
Section: Discussionmentioning
confidence: 98%
“…But our data continue to suggest that paranoia and conspiracy theorizing-even the social aspects thereof-are related to low-level domain-general primary learning mechanisms 33 which may be dopaminergically and noradrenergically mediated 34,35 . This domain general contribution to paranoia involves learning expectancies about the environment and the agents within it 36 , a process that may be guided by using oneself as a source of prior beliefs 18 . Our data represent an extension of those processes into real world social relationships.…”
Section: Discussionmentioning
confidence: 99%